Dynamic analysis of a predator–prey model of Gause type with Allee effect and non-Lipschitzian hyperbolic-type functional response| - (:unkn) unknown (World Scientific Publishing Company, 2024)
In this work, we study a predator–prey model of Gause type, in which the prey growth rate is subject to an Allee effect and the action of the predator over the prey is determined by a generalized hyperbolic-type functional response, which is neither di...
Keywords: Modelos depredador-presa; Efecto Allee